Screening Jesus of Western (Peace be Upon Him): Parables and Historical Relation with Mary Magdalene (A Critical Analysis of Christian Thinking) - Muhammad Asad Latif; Dr. Mahmood Ahmad (jihat-ul-islam, 2022)
Respecting the Prophets is necessary in every religion and desecrating them is punishable. In the present day, the contempt of the Prophets is being promoted in the Western world through film production. IN the past one hundred years the concept of presenting the live of the prophet Jesus in the film stories and web series are developing.1895 Sakladnowsky Bros, started the era of filmography, and after two months Lumiere bros as well, but they didn’t get the well audience, the dramatic irony continued and they started the filming of Jesus and showing his miracles on screens and theatres, then they got their goals and aims. Time to time western cinema showed his personality as married, as gay and as nudist Prophet, which is not only against Islamic Shari’ah and faith but its Christian religion either.in the era of 1970-1975 movies on Prophet Jesus (peace be upon him) are so popular and well-known in TV series, Netflix and movies that Western priests and nuns have fought to prevent them several times, but the pope is involved in promoting these images. Because of them, they got more fame. In Islamic point of view, it’s offensive pictorial scenario of the past whole history. In this paper will show out those superstitions and figures out his real personality through the Theological Data.